KERJASAMA BILATERAL AMERIKA SERIKAT-KANADA DALAM PROYEK KEYSTONE XL PIPELINE TAHUN 2015-2017 (STUDI KASUS: TRANSCANADA CORPORATION SEBAGAI OPERATOR PROYEK) - Silalahi, Josafat; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research explain about united states national interest politically and economically on keystone pipeline xl cooperation that operated by TransCanada Corporation since its project draft proposed in 2010 to 2018. However this cooperation attain its controversies during 2015 to 2017 when the US regime have changed while draft proposed was denied by president Obama administration in 2015 before paris agreement. this research uses liberalism perspective that emphasize non-state actor, domestic institution and related stakeholders can affect domestic decision and policy. The level-analysis of this research is nation-states as relatival of cooperation where individual, groups, organization and institution manner determined by its nation-states behavior. Theory of this research is Institutionalist Political Economic which related to foreign policy concept as an appliance that many state’s institution used to maximize the national interest either through economic, political and cultural by its policy that overlap to reach its destination. The result of this research is to show that United States make decision to continue the construction of keystone xl pipeline project are based on economic reason during the project construction and to decrease US oil dependency on Middle East, Mexico and Venezuela which intend to achieve US energy security. Keywords : Economic Political Interest, Environmental Impacts, Energy Security and Oil Dependency